If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y) + x = 145 Reorder the terms: x + (3y) = 145 Solving x + (3y) = 145 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(-3y)' to each side of the equation. x + (3y) + (-3y) = 145 + (-3y) Combine like terms: (3y) + (-3y) = 0 x + 0 = 145 + (-3y) x = 145 + (-3y) Simplifying x = 145 + (-3y)
| -21-4n=-3(7-7n) | | 1/2+2x=x-3/4 | | -2(x+4)=3(2x+8) | | 15(6-g)=g | | 4(x+6)-19=4x+5 | | -5(2x+6)/2=10 | | 5g-6-3-5g= | | 3y-4y-6y= | | 1/10(x-20)=100 | | 1.19+.39p=3.92 | | 1/3-1/3=-2 | | 9+7n=-61 | | x=7/8(Y+Z) | | -10=-4r-6r | | -8=96 | | 2[-4+1(-2z+3)]=3z-3 | | 8y-2y=3y-2 | | 5x-4x+1.6=2.7 | | 1.19+.39p=68.96 | | 4(x+6)-19=x-12 | | 1+4m-3=-18 | | -4(2a+1)=2(a+3) | | (3x+5)+(4x-2)= | | 5(-4)/-7-(-2) | | a=1/5(b+c-d) | | -8=3(x-4) | | -n+5n=8 | | 4(x+6)-19=4x-12 | | 2(4g-1)=3(g+6) | | 3m+6n-7(8m-6n)= | | 11x-(5x+7)+27=2x | | 10=x^2+x |